EVALUATING MANGO VALUE CHAINS: PRICE SPREAD, MARKETING EFFICIENCY AND CONSTRAINTS IN CHITTOOR DISTRICT, ANDHRA PRADESH - M. SAI KRISHNA (The Journal of Research ANGRAU, 2025)
The study conducted during 2024-25 in Chittoor district, Andhra Pradesh aimed at identification of various actors and activities involved in mango value chain for processing varieties along with assessment of price spread, efficiency in marketing and constraints of the actors involved. The sample size included 150 farmers and 30 intermediaries. The analysis employed value chain mapping, price spread analysis and Garrett techniques. The study identified three distinct value chains that included direct selling to processors, selling through ramp traders and selling to pre-harvest contractors. Among these, value chain 1reflecting farmers selling directly to processors was found most efficient and advantageous, offering the highest marketing efficiency (0.56) and yielding a greater sharefor producers to an extent of 55.88. Additionally, the Garrett ranking revealed that key challenges encountered by pre-harvest contractors, ramp traders, and processors across these value chains were high market price fluctuation, lack of timely payments and high requirements for working capital respectively.